Desaparecimento da Biomphalaria glabrata (Say, 1818) de Curitiba, Paraná - Luz, Ennio; Stumpf, Ilona Vivian Kleemann; Borba, Antonio Mario (Acta Biológica Paranaense, 1981)
Desaparecimento da Biomphalaria glabrata (Say, 1818) de Curitiba, Paraná